Voices through my hands: An auto-ethnographic study of the lived experiences of a South African child of Deaf adults - Harrison, Jane (Division of Disability Studies, 2019)
There is a dearth of literature about the lived experiences of hearing children of Deaf adults (CODAs) within the South African context that this study attempts to address. Most African publications examining issues of Deafness focus on the experience of Deaf people themselves. Not much attention is given to the fact that children of Deaf adults may have their own experiences which are tied to the Deafness of their parents. Through a critical examination of my own experiences as a CODA, I sought to answer the following question: In which ways has my position in my family as a CODA, my identification as a Coloured person, my gender, and the context of Apartheid South Africa influenced my sense of self? Aim: The aim of the study is to provide the reader with rich, first-person information regarding the social, political and cultural circumstances of my formative years, in the context of being female, coloured, and having parents who are Deaf, against the backdrop of the South Africa of the 1980s. I draw attention to the intersections within my life as a bicultural, Coloured female in South Africa. Using a qualitative research method, auto-ethnography (specifically an evocative ethnographic method) to generate and analyse data, I endeavour to connect my story to wider cultural, political and social processes. The analysis was informed by literature from d/Deaf studies and a conceptual framework that included models of disability, the notion of intersectionality, and theoretical ideas concerning identity formation. Objectives: I explore: i) the key elements of context that combined to shape my experience of being raised as a CODA; ii) my experiences of identity formation; iii) the ways in which the intersection of various social life attributes that include race, gender, bicultural identity, and disability have intersected to frame my lifeworld as a CODA. Methodology: I used the auto-ethnographic approach and specifically, evocative autoethnography. I drew upon the thematic analysis method to analyse the data. Findings: The auto-ethnographic material depicts my lived experience as a CODA. A key finding relates to bicultural identity formation in a context of South Africa that has been profoundly shaped by Apartheid. While negotiating a terrain that is characterised by rampant racial discrimination and the difficulties that surround an identity that is both of the Deaf and hearing worlds, my story shows up a number of active responses to my life-world, rather than a passive acceptance and internalisation of its contradictions. Conclusion: This study supports the use of auto-ethnography as a way of exploring the experience of identity formation in CODAs in a context where the ambiguities of life as a CODA are complicated by identity intersections with race, gender and culture.